Teasing apart the sources of phylogenetic tree discordance across three genomes in the oak family (Fagaceae) - Zhao Shen; Biao-Feng Zhou; Yi-Ye Liang; Jing-Shu Wang; Run-Xian Yu; Yong Shi; Shao-Jun Ling; Wen-Ji Luo; Qiong-Qiong Lin; Jing-Wei Niu; Liang-Jing Qiao; Paul S. Manos; et al. (BMC Plant Biology)
Abstract Background Gene tree incongruence is a well-documented, but the biological and analytical factors driving phylogenetic discordance remains incompletely understood. In this study, we investigated how different factors contribute to incongruence among gene trees in Fagaceae. Results Each dataset produced highly supported topologies, with Fagus and Trigonobalanus consistently placed as early-diverging lineages within the Fagaceae family. However, the cpDNA and mtDNA divided the remaining Fagaceae species into New World and Old World clades, a pattern that sharply contrasted with the phylogenetic relationships inferred from nuclear genome data. These discrepancies between the cytoplasmic and nuclear gene trees likely result from ancient interspecific hybridization within Fagaceae. The decomposition analyses revealed that gene tree estimation error, incomplete lineage sorting, and gene flow accounted for 21.19%, 9.84%, and 7.76% of gene tree variation, respectively. We further revealed that 58.1–59.5% of genes exhibited consistent phylogenetic signals (“consistent genes”), while 40.5–41.9% of genes displayed conflicting signals (“inconsistent genes”). Consistent genes showed stronger phylogenetic signals and were more likely to recover the species tree topology than inconsistent genes. However, consistent and inconsistent genes did not significantly differ in terms of sequence- and tree-based characteristics. By excluding a subset of inconsistent genes, the study significantly reduced inconsistencies between concatenation- and coalescent-based approaches. Conclusions This study illustrates how diverse factors contribute to gene tree incongruence, offering new insights into the evolutionary history of Fagaceae.